Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


Let the other number be (x) 
One of the number is P 
Mean is (2P-Q)
We know that mean = sum of observations / no.of observations 
(P+x)/2 = (2P-Q) 
(P+x) = 2(2P-Q)
(P+x) = 4P-2Q
 x = 4P-2Q -P
 x = 3P-2Q
Check :
     (P+x)/2 = (2P-Q)
     (P+3P-2Q)/2 = (2P-Q)
     (4P-2Q)/2 = (2P-Q)
     2(2P-Q)/2 = (2P-Q)
      (2P-Q) = (2P-Q)
Therefore , L.H.S = R.H.S .

0 0 0
plz mark it as best if u like it
nice one guy...
I'm girl
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts